The Use of Artificial Intelligence and the Professional Duties of German Lawyers - Rennig, Christopher (Studia Prawa Publicznego, 2025)
The rapid progress in the field of artificial intelligence, which is particularly evident to the public in the form of the emergence of large language models (LLMs) like ChatGPT, now allows the technology to be used in the field of legal services. Consequently, a growing number of lawyers are using AI to assist with legal research or drafting legal documents. This is associated with a wide range of legal issues, ranging from the regulation of legal service providers and the contractual duties of lawyers vis-à-vis their clients to the professional duties of lawyers that derive from professional codes governing the legal profession. This article shows that the professional duties of German lawyers may be affected when AI is used. After providing the reader with a general overview of the legal challenges associated with AI use by lawyers, as well as the development and current state of the legal landscape imposing German lawyers with professional duties, the article concentrates on the duty to remain independent, confidentiality obligations, in addition to the general duty to act faithfully. It also gives an overview of possible sanctions in cases of non-compliance with professional duties. By summarizing the findings, the article emphasizes remaining legal uncertainties, advising German lawyers to exercise caution when turning to AI for assistance.